Função de produção do meloeiro em resposta à fertirrigação nitrogenada e potássica na microrregião de Mossoró - Dantas, Daniel da Costa (Universidade Federal Rural do Semi-Árido, 2010)
The favourable climatic conditions associated with the use of irrigation technology put the agropolo Assu Mossoró Baraúna in a prominent position in national agribusiness. With the increase of production costs there is need for techniques that maximize the application of nutrients. Thus, obtaining yield functions in response to applications of nutrients is one of the tools that can be used for this. The objective of this work was to study the effects to the levels nitrogen and potassium applied by fertigation in the culture of cantaloupe melon type harper, in Mossoro, RN; and specific: (i) determine the levels of nitrogen and potassium (K2O) for the maximum yield, (ii) obtain the levels of maximum economic efficiency, and (iii) evaluate the effect of nitrogen and potassium on fruit quality. The statistical design utilized was randomized a block with two replicates, where the treatments were formed by the incomplete combination of two factors: levels nitrogen (N1 - 0, N2 - 38, N3 - 112, N4 - 238 kg ha-1) and levels potassium (K1 - 0, K2 – 83, K3 - 196, K4 - 365 kg K2O ha-1), obtaining the following treatments: T1 - N1K1, T2 - N1K2, T3 - N1K3, T4 - N1K4, T5 - N2K1 , T6 - N3K1, T7 - N4K1, T8 - N2K2, T9 - N2K3, T10 - N4K4. The fertilizers were applied daily from the 9th day after transplanting (DAT) until the 57th DAT. Was used the melon Caribbean Gold RZ with spacing of 2,0 x 0,3 m. In the 58 and 63 DAT the plants were harvested at for evaluation of yield. The model Z(N,K) = 20276,5 + 95,8506** N - N2 + 0,3418* 16,1171nsK – 0,0539 nsK2 to express yield total (kg ha-1), showed significant effects for test F (p <0,01), R2 = 0,80, the maximum output 28199 kg ha-1 estimated by the model, can be obtained with dosages, 140,17 kg ha-1 N and 149.51 kg ha-1 K2O; the maximum estimated net revenue of R$ 23.519,92 was obtained with a yield of 28,157 kg ha-1, applying to 135,07 kg ha-1 N and 124,79 kg ha-1 K2O. As for firmness, the nitrogen effect was quadratic, with minimum firmness obtained in the level of 100 kg ha-1 along with the higher concentrations of potassium, since for the potassium it showed a decreasing linear effect, while the soluble solids were not affected by doses of nutrients applied
Keywords: Cucumis melo L.; Função de resposta; Dosagem econômica; Cucumis melo L.; Response function; Dosage economic; CIENCIAS AGRARIAS::ENGENHARIA AGRICOLA::ENGENHARIA DE SOLO E AGUA::IRRIGACAO E DRENAGEM